2022
DOI: 10.3389/fonc.2022.965838
|View full text |Cite
|
Sign up to set email alerts
|

PKIB involved in the metastasis and survival of osteosarcoma

Abstract: Osteosarcoma is frequently metastasized at the time of diagnosis in patients. However, the underlying mechanism of osteosarcoma metastasis remains poorly understood. In this study, we evaluated DNA methylation profiles combined with gene expression profiles of 21 patients with metastatic osteosarcoma and 64 patients with non-metastatic osteosarcoma from TARGET database and identified PKIB and AIM2 as hub genes related to the metastasis of osteosarcoma. To verify the effects of PKIB on migration and invasion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…3H–J ). In summary, our results revealed a lesion-specific stromal sub-cell type in adenomyosis and found that PKIB, a gene linked to cell proliferation and invasion, effecting various cellular processes ( Wan et al, 2022 ), was significantly increased in this cluster. The study identified five stromal and two fibroblast subpopulations in adenomyosis, with a lesion-specific stromal cluster 2 expressing proliferation and invasion-related PKIB, likely contributing to the pathogenesis of adenomyosis.…”
Section: Resultsmentioning
confidence: 55%
“…3H–J ). In summary, our results revealed a lesion-specific stromal sub-cell type in adenomyosis and found that PKIB, a gene linked to cell proliferation and invasion, effecting various cellular processes ( Wan et al, 2022 ), was significantly increased in this cluster. The study identified five stromal and two fibroblast subpopulations in adenomyosis, with a lesion-specific stromal cluster 2 expressing proliferation and invasion-related PKIB, likely contributing to the pathogenesis of adenomyosis.…”
Section: Resultsmentioning
confidence: 55%